Laser micro/nano machining based on spatial, temporal and spectral control of light-matter interaction - Yu, Xiaoming (Kansas State University, 2016)
Lasers have been widely used as a manufacturing tool for material processing, such as drilling, cutting, welding and surface texturing. Compared to traditional manufacturing methods, laser-based material processing is high precision, can treat a wide range of materials, and has no tool wear. However, demanding manufacturing processes emerging from the needs of nano and 3D fabrication require the development of laser processing strategies that can address critical issues such as machining resolution, processing speed and product quality. This dissertation concerns the development of novel laser processing strategies based on spatial, temporal and spectral control of light-matter interaction. In the spatial domain, beam shaping is employed in ultrafast laser micro-processing. Zero-order Bessel beam, generated by an axicon, is used for selective removal of the back contact layer of thin film solar cells. Bessel beam’s propagation-invariance property gives rise to an extension of focal range by orders of magnitude compared to Gaussian beam, greatly increasing process tolerance to surface unevenness and positioning error. Together with the axicon, a spatial light modulator is subsequently used to modify the phase of laser beam and generate superpositions of high-order Bessel beam with high energy efficiency. With the superposed beam, processing speed can be increased significantly, and collateral damage resulting from the ring structures in the zero-order Bessel beam can be greatly suppressed. In the temporal domain, it is demonstrated that ionization in dielectric materials can be controlled with a pair of ultraviolet and infrared pulses. With the assistance of the long-wavelength infrared pulse, nano-scale features are achieved using only a small fraction of threshold energy for the short-wavelength pulse. Computer simulation based on the rate equation model is conducted and found to be in good agreement with experimental results. This study paves the way for future adoption of short-wavelength laser sources, for example in the extreme ultraviolet range, for direct laser nano-fabrication with below-threshold pulse energy. In the spectral domain, a short-wavelength infrared laser is used to generate modification in the bulk of silicon wafers, in an attempt to develop 3D fabrication capabilities in semiconductors. Issues such as spherical aberration correction and examination procedure are addressed. Permanent modification is generated inside silicon by tightly focusing and continuously scanning the laser beam inside the samples, without introducing surface damage. The effect of laser pulse energy and polarization is also investigated. These results demonstrate the potential of controlling laser processing in multiple dimensions for manufacturing purposes, and point to a future when laser can be used as naturally and efficiently as mechanical tools used today, but is targeted at more challenging problems.
Keywords: Laser material processing; Light-matter interaction; Ultrafast laser